Ecohealth research in practice innovative applications of an ecosystem approach to health - Charron, Dominique F. (Insight and innovation in international development., 2012)
This book details an ecosystem approach to health in developing regions of the world. It demonstrates how ecohealth research has led to sustained improvements and presents evidence of real changes in conditions of people, their health and their ecosystems.